A novel Fc-engineered human ICAM-1/CD54 antibody with potent anti-myeloma activity developed by cellular panning of phage display libraries - Klausz, Katja (Oncotarget, 2017)
To identify antibodies suitable for multiple myeloma (MM) immunotherapy, a cellular screening approach was developed using plasma cell lines JK-6L and INA-6 and human synthetic single-chain fragment variable (scFv) phage libraries. Isolated phage antibodies were screened for myeloma cell surface reactivity. Due to its binding characteristics, phage PIII-15 was selected to generate the scFv-Fc fusion protein TP15-Fc with an Fc domain optimized for FcγRIIIa binding. Various MM cell lines and patient-derived CD138-positive malignant plasma cells, but not granulocytes, B or T lymphocytes from healthy donors were recognized by TP15-Fc. Human intercellular adhesion molecule-1 (ICAM-1/CD54) was identified as target antigen by using transfected Chinese hamster ovary (CHO) cells. Of note, no cross-reactivity of TP15-Fc with mouse ICAM-1 transfected cells was detected. TP15-Fc was capable to induce antibody-dependent cell-mediated cytotoxicity (ADCC) against different human plasma cell lines and patients’ myeloma cells with peripheral blood mononuclear cells (PBMC) and purified NK cells. Importantly, TP15-Fc showed potent in vivo efficacy and completely prevented growth of human INA-6.Tu1 plasma cells in a xenograft SCID/beige mouse model. Thus, the novel ADCC-optimized TP15-Fc exerts potent anti-myeloma activity and has promising characteristics to be further evaluated for MM immunotherapy.